Мікро- та макроаналіз повзучості та пошкоджуваності у багатопрохідних швах - Львов, І.; Науменко, К.; Альтенбах, Х. (Проблемы машиностроения, 2013)
Розглянуто мікроструктуру багатопрохідного шва, яка складається зi стовпчастих, крупнозернистих і дрібнозернистих зон. Матеріали цих зон вважаються ізотропними. Властивості непружної поведінки металу шва мають загальний тип симетрії і описуються за допомогою анізотропної моделі повзучості. Проведені чисельні дослідження мінімального представницького об'єму за допомогою скінченноелементного комплексу ABAQUS. Рассмотрена микроструктура многопроходного шва, которая состоит из столбчастых, крупнозернистых и мелкозернистых зон. Материалы этих зон считаются изотропными. Свойства неупругого поведения металла шва имеют общий вид симметрии и описываются с помощью анизотропной модели ползучести. Проведены численные исследования минимального представительского объема с помощью конечноэлементного комплекса ABAQUS. Different zones of welded joints are subjected to different temperature fields during the process of welding. Furthermore, in multi-pass welding heating and cooling cycles, which occur due to the overlap of the pass beads, form complex microstructure. In this paper a method of evaluating creep response of the multi-pass weld based on the micro-macro mechanics approach is introduced. Multi-pass weld microstructure that consists from columnar, coarse-grained, and finegrained zones is considered. Materials of these constituents assumed to be isotropic. Weld metal properties of inelastic behavior have general type of symmetry and are described by the anisotropic creep constitutive model. To model the microstructure of the multi-pass weld metal the representative volume elements (RVE’s) with different number of passes are created and analyzed with FEA software ABAQUS. Numerical tests on uniform loading of the RVE’s are performed. Creep material properties for equivalent weld material are found for welds with different number of passes.